Efficacy and Safety of Adjunctive Recombinant Human Interleukin-2 for Patients with Pulmonary Tuberculosis: A Meta-Analysis - Lina Sheng; Xiaofei Li; Fangbin Weng; Shuang Wu; Yongxin Chen; Lianqing Lou (Journal of Tropical Medicine)
Background. The results of previous clinical trials evaluating the efficacy and safety of recombinant human interleukin-2 (rhuIL-2) for adult patients with pulmonary tuberculosis showed inconsistent results. Accordingly, a comprehensive systematic review and meta-analysis was performed. Methods. Relevant randomized controlled trials (RCTs) were retrieved by searching the PubMed, Embase, Cochrane’s Library, Web of Science, Wanfang, and CNKI databases. A random-effects model was used to combine the results. Results. 18 RCTs with 2630 patients were included in this meta-analysis. Pooled results showed that adjunctive rhuIL-2 significantly increased the odds of sputum culture conversion to negative (risk ratio [RR]: 1.27, 95% CI: 1.09 to 1.47, p=0.002, I2 = 80%), sputum smear conversion to negative (RR: 1.35, 95% CI: 1.17 to 1.57, p<0.001, I2 = 83%), radiographic focus absorption (RR: 1.17, 95% CI: 1.06 to 1.30, p=0.002, I2 = 72), and cavity closure (RR: 1.24, 95% CI: 1.09 to 1.40, p<0.001, I2 = 23). The use of rhuIL-2 was not related to any severe adverse events which led to discontinuation of the treatment. Results showed that rhuIL-2 was related to an increased risk of fever (RR: 2.46, 95% CI: 1.29 to 4.70, p=0.006, I2 = 0%). The incidence of other adverse events, such as musculoskeletal pain, hepatic injury, and renal toxicity, was not significantly different between groups (p all >0.05). Conclusions. rhuIL-2 is an effective adjunctive immunotherapy for patients with pulmonary tuberculosis.